2021
DOI: 10.1149/2.f10212if
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion in Advanced Nuclear Reactors

Abstract: Commercial nuclear power plants in the United States are light water reactors (LWRs) that use water as a coolant, with temperatures ranging between 280°C and 320°C. Water purity is tightly controlled; nevertheless, the high temperatures expose components in the water circuit to degradation by corrosion by many different types of environmental attack. Uniform corrosion occurs across the entire surface of a material and is prevalent in engineering systems to some extent. Site-specific corrosion processes, such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…They reported that the external layer was an Fe-rich spinel sometimes containing nickel (Ni) (Ni is not present in FeCrAl alloys but may still be present in the test water because of minor dissolution from the stainless steel piping and autoclave body). The presence of Al in the transition region between the Cr-rich oxide and the base metal was also reported by Was et al [19] and Ning et al [15] at higher tested temperatures of 320 • C and 360 • C, respectively. After testing tubes of Fe-13Cr-5Al for 100 days under PWR conditions, Ning et al [15] reported Al enrichment in the Cr-rich oxide.…”
Section: Matrix Matrixsupporting
confidence: 78%
“…They reported that the external layer was an Fe-rich spinel sometimes containing nickel (Ni) (Ni is not present in FeCrAl alloys but may still be present in the test water because of minor dissolution from the stainless steel piping and autoclave body). The presence of Al in the transition region between the Cr-rich oxide and the base metal was also reported by Was et al [19] and Ning et al [15] at higher tested temperatures of 320 • C and 360 • C, respectively. After testing tubes of Fe-13Cr-5Al for 100 days under PWR conditions, Ning et al [15] reported Al enrichment in the Cr-rich oxide.…”
Section: Matrix Matrixsupporting
confidence: 78%
“…The two fault modes for the mechanical seal are corrosion [ 35 ] and abrasion [ 36 ]. The cross-sectional area of the seal will increase when corrosion occurs and decrease when abrasion occurs [ 37 ].…”
Section: Structure Of the Integrated Methodsmentioning
confidence: 99%